The Impact of the Market Timing Theory on the Financial Structure of the Iraq Stock Exchange - Dr. Ahmed Risian Albahadly; Dr. Husam A. Ali Al-Hashem (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Purpose: The study aims to investigate the timing theory and its impact on the financial structure and how to interpret the decisions of the financial structure of the companies registered in the Iraq Stock Exchange. Theoretical framework: Financial structure decisions are influenced by market timing. an effect of market timing on the financial structure was not continuous over time, but rather for specific periods of time.Basically, the market timing theory according to a scale approved by Wurgler and Baker consists of five sub-dimensions: the firm size, the structure of tangible assets, profitability, the market value of the stock to its book value, the weighted rate of external financing. Design/methodology/approach: The focus of this study is to test the effect of the market timing theory on the financial structure of the Iraqi industrial companies registered in the Iraq Stock Exchange using the Baker and Wurgler (2002) model. The market timing theory is taken as independent variable, while financial leverage in terms of market- book value is taken as dependent variable. The Panel Data model and the theory equation were used to analyze the study sample of 16 Iraqi companies registered in various industrial sectors out of 43 companies during the period 2008-2020. Findings: The results showed that the market timing theory has continuous effects when using the book and market leverage. It also has an impact on the financial structure of Iraqi companies through the most important determinants of the financial structure in Iraq, including the firm size FS, asset tangibility AT, and profitability PR. New determinants were also added like market to book value MTB and external finance weighted-average WMTB in the short term. Research, Practical & Social implications: This study has taken two separate models to analyses the impact of market timing theory on the financial structure of Iraqi companies. It is searched that circulation of stock in Iraqi market is negligible due to less amount of profit given to stockholders. Originality/value: Previous studies investigated the factors affecting the capital structure of banks that are registered in Iraq stock exchange. Growth, profitability, size and liquidity are few characteristics of banks that are included in previous research work, but the significance of this study is that it incorporates two other new determinants of banks which are market to book value (MTB) and external finance weighted average (WMTB).